My home is Your Home. - Veenstra, Irene; Artists' Museum, Lodz; Het Apollohuis, Eindhoven (Heerlen : Stadsgalerij, 1993)
Panhuysen, Paul ; Homburg, Ton ; van der Putten, Hendri ; Vermeulen, Peter ; Visch, Henk ; Wevers, Kees ; Dutrieux, Daniel ; Kubiczak, Harald ; Lerman, Richard ; Marclay, Christian ; Schoutsen, Peter
My home is Your Home, Artists' Museum, Lodz, October 1-7, 1993 ; Stadsgalerij, Heerlen, 20.11 - 23.1.1994
boek